An update on the strategies used for the treatment of chronic hepatitis B in children. (3rd May 2016) - Clemente, Maria Grazia; Vajro, Pietro
ABSTRACT: Chronic hepatitis B (CHB) in children shows a variety of clinical presentations, which influence its natural course and treatment options. This report provides an overview of the ongoing strategies in pediatric CHB management. Interferon-α represents the first choice of treatment in children showing HBV replication and hepatic inflammation (immune active CHB), while the recommendation is to monitor inactive/immune-tolerant children (normal transaminases and low/absent viral replication). When circumstances preclude the use of Interferon-α and in cases of compensated/decompensated cirrhosis, entecavir for children above 2 years of age or tenofovir for children above 12 years of age are the nucleos(t)ide analogues recommended by the most recent guidelines.